Minnesota-South Dakota Beardsley Quadrangle Surveyed in 1916 - Birdseye C.H.; Floore, S.P.; Kavanagh, A.J. (Washington US Geological Survey, 1918)
Datum is mean sea level
Approximate Mean Sea Declination, 1916
Keywords: Topographic Map